Influence of aeration on nutrients removal by chlorella sp. from wastewater - Mohd Isa, Nur Zarifah; Al-Khatib, Ma'an Fahmi Rashid; Ahmad, Farah; Ahmad Raus, Raha; Alqedra, Fadi I. A. (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Interest in the usage of microalgae in wastewater treatment has been increasing as microalgae can utilize inorganic nitrogen and phosphorus for their growth. In this study, Chlorella sp. Was grown with the supply of aeration and without aeration under the same white fluorescent light and temperature of 25 °C. The results show that the growth rate of Chlorella sp. without aeration was higher than when aeration was supplied. But, the removal of ammonium and phosphate by aerated culture cells were higher with percentage removal of 86.6% and 61.05% respectively. The removal of COD showed a different trend when the removal percentage by non-aerated Chlorella sp. cells was 10% higher than aerated cells.